2007
DOI: 10.1029/2007jg000451
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenic carbon emission from a large wildfire in Oregon, United States

Abstract: We used a ground‐based approach to compute the pyrogenic carbon emissions from the Biscuit Fire, an exceptionally large wildfire, which in 2002 burned over 200,000 ha of mixed conifer forest in southwestern Oregon. A combination of federal inventory data and supplementary ground measurements afforded the estimation of preburn densities for 25 separate carbon pools at 180 independent locations in the burn area. Average combustion factors for each of these pools were then compiled from the postburn assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
224
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(243 citation statements)
references
References 33 publications
12
224
2
Order By: Relevance
“…Our results showing that C emissions from forest floor combustion can be high even in areas of relatively low severity and low change in component C stocks or overstory mortality agree with studies in similar forest types (Campbell et al, 2007;Meigs et al, 2011), and illustrate that fire also creates vertical heterogeneity in terms of effects on forest C. Our observations of large differences in pre-fire overstory and understory C stocks between plots burned at low RS severity vs. those burned at moderate or high RS severity also illustrate that loss of shrub or seedling cover, not just tree cover, can also contribute to classification as high severity (Miller et al, 2009a). A relatively high number of smaller trees contributed to the high pre-fire live tree stem density in these areas.…”
Section: Evaluation Of Contrasting Fire Severity Metricssupporting
confidence: 80%
See 2 more Smart Citations
“…Our results showing that C emissions from forest floor combustion can be high even in areas of relatively low severity and low change in component C stocks or overstory mortality agree with studies in similar forest types (Campbell et al, 2007;Meigs et al, 2011), and illustrate that fire also creates vertical heterogeneity in terms of effects on forest C. Our observations of large differences in pre-fire overstory and understory C stocks between plots burned at low RS severity vs. those burned at moderate or high RS severity also illustrate that loss of shrub or seedling cover, not just tree cover, can also contribute to classification as high severity (Miller et al, 2009a). A relatively high number of smaller trees contributed to the high pre-fire live tree stem density in these areas.…”
Section: Evaluation Of Contrasting Fire Severity Metricssupporting
confidence: 80%
“…For example, Buma et al (2014) sampled mineral soil to 10 cm in a mixed forest 9 years after wildfire in subalpine mixed conifer forest in Colorado, USA and found no effect of fire on C stock, and Miesel et al (2015) found no effect of fire on 0-10 cm mineral soil C in southern boreal forest. In contrast, Homann et al (2011) reported a loss of 10-50% (depending on the pre-fire forest management) of mineral soil C stock in the upper 6 cm after wildfire in an Oregon Douglas-fir (P. menziesii) forest, and estimates from Campbell et al (2007) indicate 2-8% loss of C in the top 10 cm mineral soil in an Oregon mixed conifer forest, where surface temperatures of >700 • C were recorded during fire. They remarked that ".…”
Section: Wildfire Impacts On Organic Horizon and Mineral Soil C And Pycmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of altered disturbance regimes may be larger than the physiological effects of altered temperatures and precipitation on growth and respiration. For example, a large fire in southwestern Oregon released 16 times as much carbon as the annual net ecosystem production of the landscape (Campbell et al 2007). In British Columbia, mountain pine beetle outbreaks attributed to climate change have switched forests from modest carbon sinks to a significant source (Kurz et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the research on the emissions and evolution of smoke from US fires has targeted prescribed fires (Burling et al, 2011;Akagi et al, 2013;May et al, 2014;Müller et al, 2016). However, wildfires burn a different mix of fuels in a different season that has more intense photochemistry and different smoke dispersion scenarios, and they typically consume more fuel per unit area than prescribed fires and can have different emission factors (EF, g compound 15 emitted/kg fuel burned ) (Campbell et al, 2007;Urbanski, 2013). For instance, Liu et al (2017) found that wildfires had an average EF for PM 1 (particulate matter with an aerodynamic diameter less than 1 micron) more than two times that of prescribed fires and that wildfire PM 1 was more OA dominated.…”
mentioning
confidence: 99%